PAID - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Pan African Institute for Development (PAID) is an international, African, nongovernmental and non-proft organization; which contributes to the promotion of integrated and participatory development for rural and urban populations. Since 1965,...